PENGARUH PLACE-BASED EDUCATION TERHADAP KETERAMPILAN MENULIS DESKRIPSI: PERAN MEDIASI PSYCHO-INDIGENOUS - Atika Gusriani; Suroso Suroso; Sudiati Sudiati; Zherry Putria Yanti; Lisa Yuniarti; Suraya Katrina (Universitas Negeri Makassar, 2026)
This study aimed to examine the effect of Place-Based Education on descriptive writing skills through the mediating role of Psycho-Indigenous, which includes emotional attachment to place and cultural perception. The study used a quasi-experimental design with a pretest–posttest control group model within an explanatory sequential mixed methods framework. The study population comprised all ten-grade students at MAN 2 Padang, and a sample of 72 students was selected using cluster convenience sampling techniques and divided into an experimental group (36 students) and a control group (36 students). The research instruments included a descriptive writing test with an analytical rubric, a place attachment scale, a psycho-indigenous reflection instrument, and a semi-structured interview guide. Data were collected through a pretest, six-week intervention, posttest, and interviews. Quantitative data were analyzed using a paired-sample t-test, independent-sample t-test, and multiple regression analysis to test mediation, whereas qualitative data were analyzed using thematic analysis techniques. The results showed that Place-Based Education significantly improved descriptive writing skills with a very large effect (Cohen's d = 1.64). Regression analysis proved that emotional attachment and cultural perception acted as partial mediators, with an increase in R² from 0.37 to 0.56. Qualitative findings revealed that direct experience with a place enriched sensory details, integrated cultural meanings, and encouraged the internalization of experiences before writing. This study concluded that Place-Based Education improved the quality of descriptive writing through the internalization of emotional and cultural spatial experiences.